Relación entre el estrés relacionado al trabajo y el desempeño laboral en el teletrabajo - Pacheco Vise, Andrés (2022)
The Work-Related-Stress can come from many sources, from the functions themselves, relationships with peers and leaders, physical space, among others. Teleworking modifies the work dynamics including new challenges and opportunities, which can represent sources of stress for workers and impact on their performance in the organization. The objective of this systematic review is to identify the relationship between Work-Related-Stress and Job Performance in the context of teleworking. For this, a search was made in the electronic databases Scopus, Ebsco, APA PsycNet, ProQuest, Springer and Science Direct. The investigations that met the proposed inclusion and exclusion criteria (n=10) were selected for analysis and the PRISMA statement (Page et al., 2020) was considered in order to ensure the transparency of research methodology. After analyzing the articles, it was found that in nine out of the ten papers there was a significant relationship between Work-Related-Stress and Job Performance in teleworking; and in one out of ten papers analyzed, it was found that the relationship was not significant. The types of relationship found between the variables were inverse association (n=5), direct association (n=2), non-significant association (n=1) and differentiated association according to the factors (n=2). It was concluded that the relationship between stress associated with work and job performance is influenced by the context in which the person operates, as well as the type of stress and the multiple causes that produce it.